Reactive Oxygen Metabolites are Closely Associated With the Diagnosis and Prognosis of Coronary Artery Disease. Issue 2 (February 2015) - Hirata, Yoshihiro; Yamamoto, Eiichiro; Tokitsu, Takanori; Kusaka, Hiroaki; Fujisue, Koichiro; Kurokawa, Hirofumi; Sugamura, Koichi; Maeda, Hirofumi; Tsujita, Kenichi; Kaikita, Koichi; Hokimoto, Seiji; Sugiyama, Seigo; et al.
Abstract : Background: Reactive oxygen species (ROS) are associated with development of coronary artery disease (CAD). However, there's no useful biomarker of ROS in CAD. Methods and Results: We recruited 395 consecutive CAD patients who were performed coronary angiography (262 male and 133 female, age 70.2±10), and we measured serum derivatives of reactive oxidative metabolites (DROM) were measured. Two hundred twenty‐seven non‐CAD patients were also enrolled. We performed follow‐up study in these 395 CAD patients and case‐control study after risk factor and 1:1 pair matching (both, n=163). As subgroup analysis, DROM were also measured at the aortic root and the coronary sinus in 59 CAD patients. DROM were significantly higher in CAD patients (n=163, median [inter‐quartile range, IQR]=338 [302 to 386]) than in risk factor‐matched non‐CAD patients (n=163, 311 [282 to 352.5], effect size=0.33, P <0.001). During a mean follow‐up period of 20 months of 395 CAD patients, 83 cardiovascular events were recorded. Kaplan‐Meier analysis showed a higher probability of cardiovascular events in the high‐DROM group (>346 U.CARR) than in the low‐DROM group (≤346 U.CARR) ( P =0.001 [log‐rank test]). Multivariate Cox hazard analysis identified ln‐DROM as an independent predictor for cardiovascular events (hazard ratio: 10.8, 95% confidence interval: 2.76 to 42.4, P =0.001). The transcardiac gradient of DROM was significantly higher in CAD patients than in non‐CAD patients (−2.0 [−9.0 to 9.0] versus 8 [−8.0 to 28.3], effect size=0.21, P =0.04), indicating that DROM production in coronary circulation is associated with development of CAD. Conclusion: DROM are increased in CAD patients and associated with future cardiovascular events. DROM might provide clinical benefits for risk stratification of CAD. Clinical Trial Registration: URL:http://www.umin.ac.jp/ctr/ . Unique identifier: UMIN000012990.